Legal Criticism of the Effectiveness of Government Policies in Reducing the Rate of Early Marriage in Paleleh District, Buol Regency - Nurliska Y. Hentu; Lucyane Djafaar; Nopiana Mozin (Fox Justi : Jurnal Ilmu Hukum, 2026)
Early marriage remains a widespread social phenomenon in Indonesia, including in Paleleh District, Buol Regency, despite the increase in the minimum age regulation through Law No. 16 of 2019. This study aims to conduct a comprehensive legal critique of the effectiveness of government policies in reducing early marriage rates and identify obstacles encountered in the field. The method used is a descriptive qualitative approach, where data is collected through observation, documentation studies, and in-depth interviews with informants from government elements and early marriage perpetrators, which are then analyzed using the theory of legal effectiveness. The results of the study indicate that the policy has not been substantially effective because the number of underage marriages remains fluctuating and high, triggered by the exploitation of marriage dispensation loopholes and the practice of unregistered marriages. In addition, it was found that cultural factors of "shame" (sirri), economic pressure, and lack of data synchronization between agencies are the main obstacles to the success of the regulation. This study concludes that positive law does not automatically change social behavior without the support of the community's legal culture, so that policy transformation that integrates sociological approaches and community-based education is needed. These findings are important as a basis for recommendations for local governments to develop child protection strategies that are more humane and address the roots of socio-cultural problems.